2016
DOI: 10.1002/2016gl067718
|View full text |Cite
|
Sign up to set email alerts
|

Large contribution of boreal upland forest soils to a catchment‐scale CH4 balance in a wet year

Abstract: Upland forest soils affect the atmospheric methane (CH4) balance, not only through the soil sink but also due to episodic high emissions in wet conditions. We measured methane fluxes and found that during a wet fall the forest soil turned from a CH4 sink into a large source for several months, while the CH4 emissions from a nearby wetland did not increase. When upscaled to the whole catchment area the contribution of forests amounted to 60% of the annual CH4 emission from the wetlands, while in a normal year t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 35 publications
3
50
0
4
Order By: Relevance
“…However, the emission peaks at Lettosuo were relatively small when compared to upland mineral soil forest sites, where emissions of up to 3.7 mg CH 4 m −2 h −1 have been observed in wet conditions (e.g., Savage et al, 1997;Lohila et al, 2016). Similarly, the maximum hourly uptake in summer at Lettosuo was rather similar to the fluxes reported for the above-mentioned upland forests (from −50 to −120 µg CH 4 m −2 h −1 at Lettosuo vs. −40 to −80 µg CH 4 m −2 h −1 at upland forests).…”
Section: Emission Peakssupporting
confidence: 71%
See 1 more Smart Citation
“…However, the emission peaks at Lettosuo were relatively small when compared to upland mineral soil forest sites, where emissions of up to 3.7 mg CH 4 m −2 h −1 have been observed in wet conditions (e.g., Savage et al, 1997;Lohila et al, 2016). Similarly, the maximum hourly uptake in summer at Lettosuo was rather similar to the fluxes reported for the above-mentioned upland forests (from −50 to −120 µg CH 4 m −2 h −1 at Lettosuo vs. −40 to −80 µg CH 4 m −2 h −1 at upland forests).…”
Section: Emission Peakssupporting
confidence: 71%
“…The average annual uptake in boreal upland forests typically varies from about 100 to 500 mg CH 4 m −2 yr −1 Dutaur and Verchot, 2007;Lohila et al, 2016), but also annual net emissions from upland forests have been reported (e.g., Sundqvist et al, 2015;Lohila et al, 2016). Thus, the net annual CH 4 exchange measured at Lettosuo (excluding the ditches) was well within the typical range of the average CH 4 sinks reported for boreal upland forests.…”
Section: Ch 4 Exchange Dynamics In a Peatland Forest 421 Annual Balmentioning
confidence: 99%
“…The methane consumption rate was also dependent on the available soil water, soil temperature and nutrient availability. Although not addressed in that model, it should be noted that if the soil water content increases enough to inhibit the diffusion of oxygen, the soil could become a methane source (Lohila et al, 2016). This transition can be rapid, thus creating areas that can be either a source or a sink of methane depending on the season.…”
Section: Soil Uptakementioning
confidence: 99%
“…The Webb-Pearman-Leuning (WPL) correction (Webb et al, 1980) was applied when applicable (Laurila et al, 2005). More details of the measurement systems and data post-processing are given in previous studies (Aurela et al, 2009;Laurila et al, 2005;Lohila et al, 2016;Peltola et al, 2013;Rinne et al, 2007). For this study, the half-hourly averages were further averaged to daily fluxes to match the time resolution of the model.…”
Section: Field Measurementsmentioning
confidence: 99%